Bench-Scale Preparation and Qualitative Analysis of Calcium Chloride from Locally Available Raw Materials - Sultana, Fauzia; Alam, Tanjila; Quader, AKMA (Journal of Chemical Engineering, 2014)
Calcium chloride has diverse industrial applications. In spite of its demand and availability of raw materials locally, there are no chemical industries in Bangladesh that produce calcium chloride as a major product. This work was undertaken to assess the feasibility of production of calcium chloride on bench-scale by limestone-hydrochloric acid process and the quality of the product. Different amounts of limestone and 35.5% hydrochloric acid (by weight) were reacted in a PVC reactor to produce calcium chloride. Solubility at different temperature, pH, and calcium content were among the parameters measured to assess the product quality. FTIR Spectroscopy was also conducted to determine the quality of the product. Solubility values of the product ranged between 96-155g/100g water for temperatures between 30-100°C; calcium content of the product was found to be 25%. DOI: http://dx.doi.org/10.3329/jce.v28i1.18101 Journal of Chemical Engineering, Vol. 28, No. 1, December 2013: 1-3